Developing Students' Worksheet-Based Science, Technology, Engineering, and Mathematics Assisted by Augmented Reality to Improve Creative Thinking - Abdur Rasyid; Wahyu Hardyanto; Saiful Ridlo; Parmin Parmin (International Conference on Science, Education, and Technology, 2022)
Abstrak. This study aims to develop Augmented Reality-assisted Science, Technology, Engineering, and Mathematics (STEM) Student Worksheets to determine the characteristics and feasibility of augmented reality STEM student worksheets and determine the improvement of students' creative thinking skills. This research method uses the Research and Development (R&D) method. The design of this study uses the Thiagarajan (4D) model. The subject of the small group trial was Semester V A, and the large-scale trial was V B. The design used is the One Group Pretest-Posttest Design. STEM Augmented Reality student worksheets are prepared by collaborating on science, technology, engineering, and mathematics content. The results of the feasibility test in terms of the feasibility of content, presentation, and language in the criteria are very suitable for use in learning activities. The readability test results showed that the STEM Augmented Reality student worksheets were easy for students to understand. The application of Student Worksheet has facilitated the improvement of students' creative thinking which consists of fluent thinking, flexible thinking, original thinking, and elaborative with moderate categories.